2006
DOI: 10.1007/s11136-006-9119-7
|View full text |Cite
|
Sign up to set email alerts
|

Are factors associated with subjective quality of life in people with severe mental illness consistent over time? — A 6-year follow-up study

Abstract: Subjective quality of life in severe mental illness 2 ABSTRACT Objective: To investigate the cross-sectional relationship between subjective quality of life and sociodemographic clinical and social factors over three points of assessment during a 6-year follow up, and to investigate longitudinal predictors of subjective quality of life. Method:We investigated a sample of people with severe mental illness (N=92), mainly with a psychosis diagnosis, at baseline and at an 18-month and 6-year follow-up. Measures Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
2
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 28 publications
5
35
2
7
Order By: Relevance
“…Our main longitudinal finding is that QOL at baseline accounted for 40% of variance in the same factor at follow-up. This is consistent with other longitudinal studies done in different clinical samples (Slade et al, 2004;Hansson and Bjorkman, 2007). Moreover, Landolt et al (2012), using a SEM approach in a groups of patients with a first-episode of schizophrenia, found that fewer unmet needs, higher depression, baseline QOL, age and gender (female) were all factors associated with higher QOL at follow-up.…”
Section: Longitudinal Findingssupporting
confidence: 88%
“…Our main longitudinal finding is that QOL at baseline accounted for 40% of variance in the same factor at follow-up. This is consistent with other longitudinal studies done in different clinical samples (Slade et al, 2004;Hansson and Bjorkman, 2007). Moreover, Landolt et al (2012), using a SEM approach in a groups of patients with a first-episode of schizophrenia, found that fewer unmet needs, higher depression, baseline QOL, age and gender (female) were all factors associated with higher QOL at follow-up.…”
Section: Longitudinal Findingssupporting
confidence: 88%
“…Patient-rated unmet needs were a stronger predictor of subsequent quality of life than social role functioning, psychopathology, satisfaction with services, and therapists' ratings of needs [31]. Hansson and Björkman [9], on the contrary, did not find any longitudinal associations between needs and quality of life.…”
mentioning
confidence: 77%
“…Cross-sectional studies [3,9,10,32,35,39] have confirmed the interrelation between unmet needs and quality of life including patients with high, medium, and low levels of functioning [3]. For met needs, the interrelation with quality of life was less consistent.…”
mentioning
confidence: 99%
“…Improved overall perceived AHR in the area of health needs may have contributed, in turn, to the decrease in the number of basic, social and service needs at T2, as these are often secondary needs linked indirectly to the quality of clinical treatment for individuals with SMDs (Korkeila et al 2005). The literature acknowledges that a reduction in psychotic symptoms improves quality of life for individuals with SMDs (Hansson and Björkman 2007;Lasalvia et al 2005). Meanwhile, the increase in overall perceived AHR regarding information on illness and treatment, as well as involvement in treatment decisions, indicates that services may have successfully integrated the principles of recovery advocated in the Quebec Mental Health Action Plan (MSSS 2005).…”
Section: Discussionmentioning
confidence: 99%